2014
DOI: 10.1242/jeb.096180
|View full text |Cite
|
Sign up to set email alerts
|

Measuring individual locomotor rhythms in honey bees, paper wasps and similar sized insects

Abstract: Circadian rhythms in social insects are highly plastic and are modulated by multiple factors. In addition, complex behaviors such as sun-compass orientation and time learning are clearly regulated by the circadian system in these organisms. Despite these unique features of social insect clocks, the mechanisms as well as the functional and evolutionary relevance of these traits remain largely unknown. Here we show a modification of the Drosophila activity monitoring (DAM) system that allowed us to measure locom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 67 publications
(85 reference statements)
1
30
0
Order By: Relevance
“…rufipes , we employed a commercially available locomotor activity recording system (LAM 16; TriKinetics, Waltham, USA). This recording method is well established for Drosophila [54, 55] and was recently adapted to monitor social insects like bees and wasps [53, 56]. One monitor (33 x 12 x 20 cm) allows the simultaneous recording of 32 individuals in an automated way for infinite time.…”
Section: Methodsmentioning
confidence: 99%
“…rufipes , we employed a commercially available locomotor activity recording system (LAM 16; TriKinetics, Waltham, USA). This recording method is well established for Drosophila [54, 55] and was recently adapted to monitor social insects like bees and wasps [53, 56]. One monitor (33 x 12 x 20 cm) allows the simultaneous recording of 32 individuals in an automated way for infinite time.…”
Section: Methodsmentioning
confidence: 99%
“…In the numerous works involving honey bee behavior, several notable subspecies differences have been identified (Guzman-Novoa et al 1996;Giannoni-Guzmán et al 2014). While many of these differences have their basis in foraging behaviors (Cakmak et al 2010) or types of resources harvested (Köppler et al 2007), they have been shown to elicit behavioral differences when exposed to non-natural laboratory settings.…”
Section: Introductionmentioning
confidence: 99%
“…To study effects of neonicotinoid pesticides on individual honey bee circadian rhythms and sleep, forager honey bees were captured at hive entrances and maintained in individual infrared activity monitors in the laboratory for up to 8 days with ad libitum access to bee candy (honey and powdered sugar, with or without the addition of thiamethoxam or clothianidin) 19 . Neonicotinoids in the food ranged from 0-140 ng/g (or parts per billion, ppb), which is within the concentration range reported in flower nectar and pollen encountered by foraging bees [20][21][22][23] .…”
Section: Resultsmentioning
confidence: 99%